The Effect of Training on First Aid for Cardiac Arrest on Knowledge and Readiness of Cadres to Provide Emergency Aid to Cardiac Arrest Victims in the Community - Trisyani , Yanny; Emaliyawati, Etika; Nuraeni, Aan; Anna , Anastasia; Eli Kosasih, Cecep; Mirwanti, Ristina; Nurhamsyah, Donny; Prawesti, Ayu; Sugiharto, Firman (Journal Of Nursing Practice, 2026)
Background: The incidence of cardiac arrest or Sudden Cardiac Arrest (SCA) in the community that cannot be saved increases every year. This is because they do not get the right and fast action due to the community's ignorance and inability to assist. Objective: This study aimed to evaluate health education on increasing knowledge and readiness of respondents in helping cardiac arrest victims. Methods: This study used a pre-experimental design with a one-group pre-post test approach to 52 respondents, namely the general public. The research sample was recruited using convenience sampling techniques. The sample was given health education on basic life support (BLS) and cardiac arrest management directly with several interactive sessions using visual aids such as posters and presentation slides. Data collection used a valid and reliable questionnaire (Knowledge and Readiness to Help). Data were analyzed univariately through frequency distribution, central tendency, mean difference, and bivariate tests using paired sample t-tests. Results: There was an increase in respondents' BLS knowledge from 6.87 to 11 (p<0.001) and readiness to help, with an average score increasing from 60.4 to 63.3 (p=0.002). These results indicate that health education can increase knowledge about BLS and readiness to help respondents. Research results show that readiness to act in emergencies depends on more than theoretical understanding; it also requires practical training, self-confidence, and direct experience. Conclusion: Health education significantly improved public knowledge and readiness to provide first aid for cardiac arrest victims. These findings indicate that structured Basic Life Support (BLS) education is effective in strengthening community preparedness and timely emergency response. Integrating regular and practical BLS training into community health programs may further enhance public capacity to respond to cardiac arrest events.